Literary border crossings - Proulx, Patrice J. (2011)
Literary border crossingsReconceptualizing Montesquieu’s Lettres persanes in Lise Gauvin’s Lettres d’une autre and Chahdortt Djavann’s Comment peut-on être français ? (2011) 1er septembre 2013, par Proulx, Patrice J. Paula Ruth Gilbert et Miléna Santoro (dir.), Transatlantic passages. Literary and cultural relations between Quebec and francophone Europe, Montréal, Kingston, Londres et Ithaca, McGill-Queen’s University Press, 2011, p. 122-135.
Keywords: exportSPIP